Intraocular Pressure Is a Poor Predictor of Hydration Status following Intermittent Exercise in the Heat - Stewart, Ian B.; Dias, Brittany; Borg, David N.; Bach, Aaron J. E.; Feigl, Beatrix; Costello, Joseph T. (Frontiers in Physiology, 2017)
Current hydration assessments involve biological fluids that are either compromised in dehydrated individuals or require laboratory equipment making timely results unfeasible. The eye has been proposed as a potential site to provide a field-based hydration measure. The present study evaluated the efficacy and sensitivity of intraocular pressure (IOP) to assess hydration status. Twelve healthy males undertook two 150min walking trials in 40°C 20% relative humidity. One trial matched fluid intake to body mass loss (control, CON) and the other had fluid restricted (dehydrated, DEH). IOP (rebound tonometry) and hydration status (nude body mass and serum osmolality) were determined every 30min. Body mass and serum osmolality were significantly (p<0.05) different between trials at all-time points following baseline. Body mass losses reached 2.5±0.2% and serum osmolality 299±5 mOsmol.kg-1 in DEH. IOP was reduced during DEH (150min: -2.7±1.9mmHg; p<0.05) but remained stable in CON (150min: -0.3±2.4mmHg). A significant trial by time interaction was observed for IOP (p = 0.042), indicating that over the duration of the trials IOP declined to a greater extent in the DEH compared with the CON trial. However, using an IOP value of 13.2 mmHg to predict a 2% body mass loss resulted in 57% of the data being correctly classified (sensitivity 55% and specificity 57%). The use of ΔIOP (-2.4 mmHg) marginally improved the predictive ability with 77% of the data correctly classified (sensitivity: 55%; specificity: 81%). The present study provides evidence that the large inter-individual variability in baseline IOP, and in the IOP response to progressive dehydration, prevent IOP, as measured by rebound tonometry, as an acute single assessment marker of hydration status.